EFFECT OF CHALK-BOARO MATHEMATICAL SET ON STUDENT’S PERFORMANCE IN FURTHER MATHEMATICS IN SOME SECONDARY SCHOOLS IN BOSSO LOCAL GOVERNMENT AREA OF NIGER STATE, NIGERIA - Gana, C S (Sokoto Educational Review, 2011)
This study investigated the effect of chalkboard mathematical set an instructional material on the performance of the student in further mathematics in a senior secondary school in a sampled area. Two secondary schools in Bosso Local Government Area of Niger State were sample. In Educational setting, most secondary school teachers teach through lecture method the finding shows that secondary school students perform poorly in most subjects (especially further mathematics which could be associated with the method of teaching the subject). This study confirmed the suggestions of some Educationist that teaching students with instructional materials will arouse the interest of students and will improve teaching and learning in all classrooms. The study adopted the pretest experimental control group design. The sample population was made up of one hundred and twenty (120) senior secondary schools class Two (SSIl) Students randomly selected from two secondary schools in Bosso Local Government Area of Niger State, Nigeria. Pretest and post-test questions were administered to both groups and scores based on a hundred per cent (100%). The result is evidently shown in the highest post-test mean score of 56.4 of the experimental group compared to the control group mean score of 50.2. One hypothesis was tested at =0.05 level of significance. Data collected were based on the pretest of the descriptive statistics via Mean, Standard Deviation and t-test to arrive at the result in the study.